PENERAPAN MODEL TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR TEKS PROSEDUR PADA SISWA KELAS IV SD NEGERI 1 BAMBI PIDIE - Tuti Susanda; Intan Safiah; Hasniyati Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the low learning outcomes of Grade IV students at SD Negeri 1 Bambi in the topic of procedural text. Out of 22 students, 14 students (63.6%) had not yet met the Learning Objective Achievement Criteria (KKTP) of 75, with a class average score of 68.5. This study aims to (1) describe teacher activity in implementing the Talking Stick model, (2) describe student activity in implementing the Talking Stick model, and (3) determine the improvement in student learning outcomes. This research employed a qualitative approach using Classroom Action Research (CAR) consisting of two cycles. The results showed improvements in all three aspects. Teacher activity increased from 86.90% (Good) in Cycle I to 96.43% (Very Good) in Cycle II. Student activity increased from 86% to 97.62%. Student learning outcomes improved from an average of 69.41 with 31.82% classical completeness in Cycle I to 89.55 with 100% in Cycle II. The Talking Stick model has been proven effective in improving activity and learning outcomes on procedural text in Grade IV of SD Negeri 1 Bambi Pidie